Safety, Adherence, Enzymatic Activities, and Application Effects of Oral Probiotic Candidates for Shortfin Eel (Anguilla bicolor bicolor) - Andita Ratih Dewanti; Anggi Octari Putri; Indah Istiqomah Istiqomah; Alim Isnansetyo (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research The shortfin eel elver bicolor bicolor was tested for the safety of Enterobacter sp. JC05, Lactococcus sp. JAL37, and Bacillus sp. PCP1 The ability of bacterial strains to adhere to epithelial cells of shortfin eel epithelial cells was demonstrated The bacterial strains' proteolytic, cellulolytic, and lipolytic activities were detected Oral administration of the bacterial cocktail lowered overall viable bacterial count but did not affect the shortfin eel's intestinal histological characteristics   Abstract Aquaculture of the shortfin eel (Anguilla bicolor bicolor) has been plagued by low survival and growth due to the low tolerance to water quality and feed. The microbiota and shape of the fish intestinal tract influence the immune and digestive systems. The use of bacterial probiotics is fascinating to enhance the digestion system. This study aimed to characterize bacterial probiotic candidates' safety and potential probiotic features for shortfin eel (A. bicolor bicolor) aquaculture. The safety, adherence, and enzymatic activity of three bacterial strains (Bacillus sp. PCP1, Lactococcus sp. JAL 37, and Enterobacter sp. JC05) were investigated. An oral application test was performed on shortfin eel (n=880, 15 g) every four days with 0, 3x103, 3x105, and 3x107 CFU/g diet dosages in quadruplicates for two months. At the end of the experiment, total cultivable bacteria and intestinal morphology were assessed. Based on the hemolytic test and intraperitoneal injection, the bacterial strains were considered harmless. In an in vitro investigation, the bacteria attached to shortfin eel intestinal epithelial cells. An agar diffusion method validated the proteolytic, lipolytic, and cellulolytic activities. In vivo feeding tests with the bacterial cocktail lowered the total viable bacteria in the gut while preserving the gut histology. Bacterial strains of the present study are potential probiotic candidates for shortfin (A. bicolor bicolor) aquaculture.